PENGARUH LATAR BELAKANG PENDIDIKAN TERHADAP PROFESIONALISME GURU PRODUKTIF DI SMK NEGERI 2 KUPANG - Edyan, Roly; Asrial; Yohanes Gampur (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
State Vocational High School (SMK) 2 Kupang is a vocational education institution locatedat Jalan A. Yani No. 48 Fatubesi, Kupang City, East Nusa Tenggara. This school offers various expertise programs designed to prepare students to be ready to enter the workforce or continue their education to a higher level. The expertise programs consist of Geomatics, Electrical Power Installation Engineering, Machining Engineering, Welding, Automotive Light Vehicles, Motorcycle Business and Engineering, Audio Video, Sanitation Construction and Building Maintenance, Bridge Construction and Irrigation, Design, Modeling and Building Information, Multimedia, Solar Hydro and Wind Energy Engineering, and Electronics. This study aims to (1). To determine the educational background of productive teachers at SMKN 2 Kupang. (2). To determine the significant influence between the educational background of teachers on the professionalism of SMKN 2 Kupang teachers. Ex post facto research method, with a quantitative approach. Simple random sampling technique, sample size 25 teachers. Data collection techniques are questionnaire distribution and documentation analysis. Descriptive statistical data analysis techniques, correlation, regression and hypothesis. The results of the study indicate that there is a positive and significant influence between educational background and the professionalism of productive teachers at SMKN 2 Kupang. Based on the results of the F test, the calculated F value was 14.159 with a significance of 0.01 < 0.05, so Htherejected and Ha accepted. The probability of t count (3.763) < t table (2.807) and the significance value of the Teacher Educational Background Condition variable is 0.01 < 0.05, then Htherejected and Ha accepted.